Legality Of Land And Building Objects In The Tomb Of Ki Ageng Gribig, Malang City - Isdiyana Kusuma Ayu; Pinastika Prajna Paramitha; Lina Alfiana; Isdian Anggraeny (Universitas Widya Gama Malang, 2023)
The Ki Ageng Gribig Tomb area is planned to be developed as a santri village that presents a village model that carries a religious theme. People come to travel or to trade around the area. Merchants who will sell around the tomb area of Ki Ageng Gribig will live on land. If it lasts for a long time, the merchant will use a vacant lot to sell and will harm the original owner. So it is necessary to have awareness of the indigenous people living in the area around the ki Ageng Gribig tomb area to have proof of land ownership rights. The purpose of the study was to find out and analyze related to evidence of land ownership owned by the community living around the Tomb of Ki Ageng Gribg. Another purpose is to describe the urgency of ownership of the legality of land or buildings for people living around the Ki Ageng Gribig Tomb area. This research uses empirical juridical research methods with a sociological juridical approach. The result of this study is that before the birth of uupa, residents who lived around the Tomb area of Ki Ageng Gribig already had proof of rights in the form of eigendom rights and had been converted into property rights. The ownership of evidence of land ownership is very important because residents will get their full rights if one day the development of the Ki Ageng Grbig Tomb Area takes place. The certificate of land rights will be strong evidence for those who hold it, so that when the development of the Ki Ageng Gribig tomb area becomes a religious tourism village, the surrounding community will get reimbursement by the provisions of the Land Acquisition.